Manajemen Sekolah di Era Pandemi Covid-19 pada Madrasah Aliyah Pondok Pesantren Darul A'mal Metro Lampung - Sutrisno, Sutrisno (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
Covid-19 is the world's desire that provides challenges as well as opportunities for the world of education. Educational institutions are dealing with the COVID-19 pandemic in various ways. School management in the pandemic era is proof of the success and failure of educational institutions. Madrasah Aliyah Pondok Pesantren Darul A'mal Metro Lampung is a school institution that implements face-to-face learning in the midst of the COVID-19 pandemic. The problem that arises at the same time as the purpose of this research is how good management is in carrying out these teaching and learning activities. The research method used in this research is field research, with a phenomenological approach and the method is descriptive-qualitative. Interview, observation and documentation as a way to obtain data. The result of this research is that learning at Madrasah Aliyah Pondok Pesantren Darul A'mal Metro Lampung is done face-to-face, but still uses strict health protocols. Some of the findings that researchers found were that during the covid-19 pandemic, students were increasingly lazy to study and their discipline and achievement decreased. Existing obstacles include: difficulties in controlling guests / guardians of students in complying with the rules of the pesantren, some students and teachers do not comply with health protocols, students do not maintain health protocol facilities provided by schools/madrasah.